Central nervous system involvement in Anderson–Fabry disease: a clinical and MRI retrospective study. Issue 11 (5th June 2008) - Buechner, S; Moretti, M; Burlina, A P; Cei, G; Manara, R; Ricci, R; Mignani, R; Parini, R; Di Vito, R; Giordano, G P; Simonelli, P; Siciliano, G; et al.
Abstract : Background: Anderson–Fabry disease (AFD) is an X-linked lysosomal storage disorder caused by deficiency of alpha-galactosidase A. Central nervous system (CNS) manifestations consist mainly of cerebrovascular events. Brain MRI results are often abnormal. Purpose: The aim of the study was to describe CNS involvement in a group of Italian patients with AFD. Methods: Clinical and brain MRI data of 43 patients with AFD (25 men, 41.94±10.83 years old and 18 women, 52.48±17.50 years old) were analysed retrospectively. 17 male patients and 7 female patients were under treatment with enzyme replacement therapy (ERT). Results: All 43 patients had signs or symptoms of AFD. 16 men (64%) and 13 women (72%) demonstrated CNS involvement, although with varying severity. Overall, 6 men and 5 women had suffered from cerebrovascular accidents with an age at onset of 33.64±13.65 years and 53.68±11.71 years, respectively. Brain MR images were abnormal in 16/25 men and in 13/16 women. During CNS monitoring, some patients receiving ERT (5/17 men and 2/6 women) demonstrated neurological deterioration, especially those who had presented with cerebrovascular disease already before starting ERT. Conclusions: The study demonstrated a high frequency of CNS involvement in homozygous and heterozygous AFD patients, often characterised by early age at onset and abnormal brain MRIs. At present, ERT is widely used; however, potential beneficent effects may be disguised by the progression of irreversible pathology in short-term follow-up. Therefore, primary and secondary prophylaxes of cerebrovascular disease are extremely important.